Commentary on “An Information-Theoretical Method for Comparing Completions of Contrapunctus XIV from Bach’s Art of Fugue” - Acevedo, Stefanie (Empirical Musicology Review, 2023)
Information entropy can be a powerful tool for analyzing differences in musical style as suggested in Paz et al. (2022). The application of such a tool, however, requires unambiguous operationalization of the variables being measured, and establishment of clear relations between the variables and the distinguishing features of the style. Without these, interpreting entropy, or any other relative measure of difference, leads to no useful conclusions regarding the similarity between style.